Assessment of Pharmacist Intervention Among Post Hospital Discharge Patients with Moderate and Severe Acute Heart Failure - Helen Faris Marzoog; Manal Khalid Abdulridha; Shokry Faaz Nassir (College of Pharmacy / Mustansiriyah University, 2019)
Background: Acute heart failure is the most common cause for hospitalization and the third highest cause of hospital readmission with nearly quarter of patients being re hospitalized within 30 days after discharge. Implementation of Clinical pharmacists in coordinated inpatient care, discharge planning and outpatient care result in significant improvements in adverse drug events reduction, medication adherence, quality of life and patient knowledge. Objective: Evaluating pharmacist- based program for patients with moderate and sever acute heart failure via improving summary discharge in reduction hospital readmission, enhancing medications adherence and improve quality of life. Patients and Methods: This prospective study was carried out under interventional pharmacist- based program carried out on 50 patients whom completed this study, they were randomly allocated to two groups, program group who are receiving program for assessment and review starting from 30 minutes pre hospital discharge till 12 weeks. The control group on usual care which include physician-based discharge summary, routine laboratory test without pharmacist intervention (25 patients for each group). Result: After 12 weeks of follow up among program patients in comparison with control group, study findings revealed  significant improvement in self-care heart failure index domains (maintenance,  management, confidence and total  SCHFI score (P=0.001) in both moderate heart failure (NYHAIII) and severe heart failure (NYHAIV) groups, also increase in domains of belief medication questionnaire whether specific necessity and specific concern domains (P=0.001) or decreased in general harm and general overuse (P=0.001) in both moderate and severe heart failure. Moreover, increase in all domains of WHO quality of life questionnaire (WHOQOL) (P=0.001) in both moderate and sever heart failure with predominant improvement in moderate heart failure. Both serum brain natriuretic peptide (P=0.001) and cardiac troponin I (P<0.01) level were decreased in patients with moderate and severe HF and ejection fraction was improved (P=0.03) only among patients with severe HF of program group. Conclusion: Implementing pharmacist- based management program for patients with moderate and severe acute heart failure via summary discharge markedly improve disease awareness, medication adherence, reduced hospital readmission and total mortality at the end-line of study among intervention patients compared to the usual care.